Demineralization detection in orthodontics using an ophthalmic optical coherence tomography device equipped with a multicolor fluorescence module - Şen, Sinan; Erber, Ralf; Orhan, Gül; Lux, Christopher J.; Zingler, Sebastian (Clinical oral investigations, 2019)
Demineralizations such as white spot lesions are among the most prevalent side effects during orthodontic treatment. Fluorescence devices, including quantitative light-induced fluorescence (QLF), exploiting the intrinsic fluorescence of enamel and teeth and most recently optical coherence tomography (OCT) were introduced for early demineralization detection. In addition to near-infrared OCT scanning, multicolor modules allow for imaging with different laser wavelengths and the detection of reflective- and fluorescent light. The aim of this study was to evaluate a modified multicolor ophthalmic OCT device for the detection of early carious lesions in vitro and in vivo.